Peningkatan Hasil Pertanian Tanaman Hortikultura melalui Pelatihan Smart Farming di Tomohon - Andi Ikhtiar Bakti; Ade Yusupa; Tika Putri Agustina (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The Maulit Farmers Group, located in Tomohon City, North Sulawesi, has the potential for horticultural farming due to its geographical location on the slopes of Mount Lokon. The challenges faced include limited funds and technology knowledge and skills in applying smart farming technology which impact production results. The purpose of this training activity is to implement a smart farming system to optimize horticultural crop yields, increase the income of Maulit Farmers Group members, and empower the surrounding community. The training methods include program socialization, training on smart farming systems, business strategy and digital marketing, and horticultural crop cultivation, followed by program mentoring and evaluation. After the training activities, there was an increase in knowledge and skills: from a pre-test result where 80% did not understand the technology, to a post-test result showing 90% who understood and could independently operate smart farming technology. Based on these results, the training activity achieved the targeted outcomes is independence in implementing smart farming technology to enhance agricultural production and initiate sustainability for farmer groups located in the surrounding areas.